Integrated gut microbiota and metabolomics analysis reveals the antitumor effects of ergosta-4,6,8(14),22-tetraen-3-one purified from the medicinal fungus pholiota adiposa in tumor-bearing mice - Liu, Boyuan; Qin, Junsen; Zheng, Shan; Zhang, Jiaxin; Hu, Xuemei; Wang, Xiaoyan; Liu, Yan (Frontiers in Pharmacology, 2025)
ObjectiveThis study aims to investigate the antitumour mechanism of ergosta-4,6,8(14),22-tetraen-3-one (ETO), extracted from Pholiota adiposa, in H22 tumour-bearing mice through integrated metabolomics and gut microbiota systems analysis.MethodsAfter establishing the H22 tumor mouse model, we performed serum metabolomics through nontargeted UHPLC-HRMS and conducted gut microbiota profiling.ResultETO exhibited significant antitumor effects, with tumor inhibition rates of 59.74% (low dose) and 76.10% (high dose).Untargeted metabolomics revealed that molecules downstream of the tricarboxylic acid cycle, arachidonic acid and linoleic acid were upregulated. Gut microbiota analysis revealed ETO-mediated enrichment of beneficial bacteria (Firmicutes and Lactobacillus) and suppression of the harmful bacterial species Bartonella. Integrative analysis demonstrated a negative correlation between indole-3-acetonitrile and Bartonella.ConclusionETO can inhibit the growth of tumor cells, and its effect on liver and kidney damage is less than that of CTX. Linoleate, and L-tryptophan emerged as potential therapeutic targets, while Firmicutes and Lactobacillus enrichment suggests gut microbiota-mediated antitumor activity, providing novel insights for hepatocellular carcinoma treatment.